Safety and Feasibility of Long-Distance Aeromedical Transport of Neonates and Children in Fixed-Wing Air Ambulance - Veldman, Alex; Krummer, Stefanie; Schwabe, Dirk; Diefenbach, Michael; Fischer, Doris; Schmitt-Kästner, Sophie; Rohrbeck, Cornelia; Pannu, Ruby (Journal of Pediatric Intensive Care, 2021)
In cases of critical injury or illness abroad, fixed-wing air ambulance aircraft is employed to repatriate children to their home country. Air ambulance aircraft also transport children to foreign countries for treatment not locally available and newborns back home that have been born prematurely abroad. In this retrospective observational study, we investigated demographics, feasibility, and safety and outcomes of long-distance and international aeromedical transport of neonates and children. The study included 167 pediatric patients, 56 of those preterm neonates. A total of 41 patients were ventilated, 45 requiring oxygen prior to the transport, 57 transferred from an intensive care unit (ICU), and 48 to an ICU. Patients were transported by using Learjet 31A, Learjet 45, Learjet 55, and Bombardier Challenger 604, with a median transport distance of 1,008 nautical miles (NM), median transport time of 04:45 hours (median flight time = 03:00 hours), flight time ≥8 hours in 15 flights, and transport time ≥8 hours in 29 missions. All transports were accompanied by a pediatric physician/nurse team. An increase in FiO2 during the transport was documented in 47/167 patients (28%). Therapy escalation (other than increased oxygen) was reported in 18 patients, and technical adverse events in 3 patients. No patient required CPR or died during the transport. Clinical transport outcome was rated by the accompanying physician as unchanged in 163 transports, improved in 4, and deteriorated in none. In summary, international, long-distance transport of neonatal and pediatric patients performed by experienced and well-equipped transport teams is feasible. Neither major adverse events nor physician-rated clinical deteriorations were observed in this group of patients.
Keywords: pediatric; neonatal; transportation; air ambulance